THE MAXIMAL ROLE OF LIBRARY AS EDUCATION MEDIA FOR STUDENTS - Lisa Irwit Sari (P3M STAIN Kudus, 2016)
This paper aims to describe how the role of the library for students is. And it also aims to describe how to maximize the role of the library as an educational media using descriptive analysis method. Maximizing the library management for student must be supported by a professional management and modern library by the school so that people can see concrete changes of a library. There are several things that can be done by the school in order to change the social stigma of the existence of the school. First, the library should be managed more professional. Second, the library should be developed with adequate facilities. Based on the role and duties of the library, the library needs to conduct educational programs or users so that the available library collection can be disseminated and used effectively and efficiently.